The impact of sperm morphology on the outcome of intrauterine insemination cycles with gonadotropins in unexplained and male subfertility. (February 2016) - Erdem, Mehmet; Erdem, Ahmet; Mutlu, Mehmet Firat; Ozisik, Seckin; Yildiz, Sule; Guler, Ismail; Karakaya, Cengiz
Abstract: Objective: To determine the impact of sperm morphology on success of intrauterine insemination (IUI) in unexplained and male subfertility. Study design: Basal and post-wash normal percentage of sperm with normal morphology was assessed prospectively in 412 couples with 530 IUI cycles who underwent ovarian hyperstimulation with gonadotropins. The primary outcome was live birth per cycle. Receiver operating characteristics (ROC) curves were used to determine the effectiveness of sperm morphology to predict live birth in IUI cycles. Results: Normal sperm morphology (%) after preparation was higher in patients with live birth (5.4 ± 4.5 vs 4.3 ± 4.1; respectively, p  < .05) in study population. In male subfertile group, normal sperm morphology before and after sperm preparation was higher in patients with live birth (1.3 ± 1.4 vs 0.6 ± 0.9; p  < 0.001 and 4.6 ± 4.4 vs 1.9 ± 2.2; p  < 0.01, respectively). However, both basal and post-wash normal sperm morphology (%) were similar in patients with and without live birth in unexplained group. The best cut-off value for normal sperm morphology (%) to predict live birth was 4.5% in male subfertile group with a sensitivity of 50.6% and specificity of 61.7%. Conclusion: Morphological evaluation is not a reliable parameter alone for predicting pregnancy outcome in unexplained infertility. In male subfertility, post-wash normal sperm morphology percentage higher than 4.5 increases the probability of live birth.